Supplemental irrigation from harvested rainwater to enhance yield and economic returns from wheat in sub-montane region of Jammu, India - SHARMA, K. R.; SHARMA, VIKAS (Journal of Soil and Water Conservation, 2021)
A study was carried out to study impact of rainwater harvesting and supplemental irrigations on wheat production in the rainfed sub-montane region of Jammu, India. A cemented rainwater harvesting tank was constructed in the selected area, with the slopy areas forming the catchment and the agricultural fields in the plain zone as command area. The treatments comprised of three irrigation levels (zero, one and two) and two fertilization levels. Both the application of fertilizers and irrigations alone resulted in increase in grain and straw yield as well as uptake of N, P and K. However, the combination of two irrigations along with recommended dose of fertilizers (RD) gave higher yields by more than 200% over the treatment where no irrigation was applied, as result of increased nutrient uptake. In the second year of experimentation the above normal rainfall received during the initial months of crop growth reduced the impact of irrigation levels (although still significant), with increase in grain yields being less than 50%. During the first year of experimentation the economic returns were maximum for RD where two irrigations were applied, however, in the second year, due to above average rainfall, returns were higher where no irrigations were given, as the construction and maintenance cost of rainwater harvesting tank were not incurred in this case.